2015
DOI: 10.2310/7290.2015.00003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of the Human Pulmonary Vascular Endothelium Using an Adrenomedullin Receptor Ligand

Abstract: This phase I study (NCT01539889) evaluated the safety, efficacy, and dosing of PulmoBind for molecular imaging of pulmonary circulation. PulmoBind is a ligand of the adrenomedullin receptor abundantly distributed in lung capillaries. Labeled with 99mTc, it allows single-photon emission computed tomographic (SPECT) imaging of lung perfusion. In preclinical studies, PulmoBind scans enabled detection of lung perfusion defects and quantification of microcirculatory occlusion caused by pulmonary hypertension. Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Animals were anesthetized by isoflurane (1.5–2%). 99m Tc-labeled PB (37–58 MBq) was prepared as previously described in details 6 and intravenously injected in a volume of 300 μL via the caudal vein. In vivo whole-body biodistribution of radioactivity was measured by a nuclear medicine camera (Ecam, Siemens) equipped with an on-board computer and a low-energy high resolution parallel-hole collimator.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animals were anesthetized by isoflurane (1.5–2%). 99m Tc-labeled PB (37–58 MBq) was prepared as previously described in details 6 and intravenously injected in a volume of 300 μL via the caudal vein. In vivo whole-body biodistribution of radioactivity was measured by a nuclear medicine camera (Ecam, Siemens) equipped with an on-board computer and a low-energy high resolution parallel-hole collimator.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, 99m Tc-MAAs obstruct small arteries in subjects with an already reduced lung perfusion with inherent risks associated with the use of a human-derived product. PulmoBind (PB) is a novel molecular SPECT imaging agent that distributes according to the lung capillaries perfusion by binding to the vascular endothelium 16 . PB is a specific ligand of the adrenomedullin receptor (AM 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its antagonistic properties it is only binding but not activating ADM receptors in the vascular endothelium. Therefore, it allows the detection of lung perfusion defects and microcirculatory occlusions in early stages of the disease, which has been already proven in phase I clinical trials [200].…”
Section: Cancermentioning
confidence: 99%
“…In pre-clinical studies, 99m Tc-PulmoBind displays all the qualities desired of a molecular imaging agent in nuclear medicine: sizeable first pass and prolonged uptake by the lungs and quick plasma clearance with elimination by both the liver and kidneys [ 51 ]. A human phase I study of PulmoBind in normal human subjects was recently completed (Clinicaltrials.gov NCT01539889) [ 54 ]. We demonstrated that PulmoBind is safe while providing superior quality lung imaging compared to 99m Tc-MAA.…”
Section: Molecular Imaging Of the Pulmonary Vasculaturementioning
confidence: 99%